Laparoscopic Diagnosis of Adenocarcinoma of the Appendix Mimicking Serous Papillary Adenocarcinoma of the Peritoneum. (9th December 2013) - Yoshimura, Mayumi; Terai, Yoshito; Konishi, Hiromi; Tanaka, Yoshimichi; Tanaka, Tomohito; Sasaki, Hiroshi; Ohmichi, Masahide
Abstract : Primary carcinoma of the vermiform appendix is a rare disease with few clinical symptoms. Accordingly, preoperative diagnosis of appendiceal cancer is challenging because of the lack of specific symptoms. We herein report a case of appendicular adenocarcinoma found unexpectedly during laparoscopic surgery in a 69-year-old Japanese female patient diagnosed with serous papillary adenocarcinoma, in order to determine whether optimal cytoreduction could successfully be achieved at the time of primary surgery. We performed diagnostic laparoscopic surgery in order to make a correct diagnosis based on the histological tissue. The vermiform appendix was found to contain a tumor measuring 1.5 cm wide and 4.5 cm long. Laparoscopic appendectomy, partial omentectomy, and partial resection of the lesion in the peritoneum were performed. The histological diagnosis was mucinous adenocarcinoma of the vermiform appendix, and the stage was T4NxM1. The patient received adjuvant chemotherapy with mFOLFOX 6 (5FU, leucovorin, and oxaliplatin). She achieved stable disease and was alive with disease eleven months after surgery. We therefore recommend that gynecologists should not rule out the possibility of appendiceal cancer, even in cases with preoperative findings similar to those of serous papillary adenocarcinoma of the peritoneum with peritoneal disseminated tumors.